A star-shaped polyaryletherketone resin ST-PEKKS-TH and its preparation method and use

By using triphenoxybenzene (TPOB) as a branching agent, a star-shaped polyaryl ether ketone resin ST-PEKKS-TH with a high glass transition temperature and a low melting temperature is prepared, which solves the problem of existing resins during processing and molding. solve the problems of high melting temperature and low glass transition temperature, and improve the high and low temperature resistance and solubility of the resin.

CN117843929BActive Publication Date: 2025-01-21FUJIAN JUYUXIN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310558885.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-05-17
Publication Date
2025-01-21
Estimated Expiration
2043-05-17

AI Technical Summary

Technical Problem

The existing polyaryletherketone resins have problems with high melting temperature and low glass transition temperature during processing and forming, which leads to difficult processing and insufficient fusion thermal oxidation stability.

Method used

Using triphenoxybenzene (TPOB) as a branching agent, it reacts with aryl ethers and aromatic acid chlorides in a catalyst solvent system. Through Friedel-Crafts acylation reaction and complexation reaction, a high glass transition temperature, Star-shaped polyaryl ether ketone resin ST-PEKKS-TH with low melting temperature.

Benefits of technology

It increases the glass transition temperature of the resin, lowers the melting temperature, enhances high and low temperature resistance and solubility, and shows good solubility and melt thermal oxidation stability in common low-toxic organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117843929B_ABST
    Figure CN117843929B_ABST
Patent Text Reader

Abstract

The present invention provides a polyaryletherketone resin ST-PEKKS-TH and a preparation method and use thereof, belonging to the technical field of special engineering plastics. The structural formula of the polyaryletherketone resin is shown in Formula I, wherein A 2 For aromatic diacyl structure, B 2 For aromatic ether structure, B 3 The polyaryletherketone resin of the present invention or the polyaryletherketone resin obtained by the preparation method has the advantages of high glass transition temperature, low melting temperature, good high and low temperature resistance, good solubility in common low-toxic organic solvents, good melt thermal oxidation stability, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special engineering plastics, and specifically relates to a star-shaped polyaryletherketone resin ST-PEKKS-TH and a preparation method and application thereof. Technical Background

[0002] Polyaryletherketone resin (PEAK) is a kind of thermoplastic polymer material whose main chain is composed of aromatic ether and aromatic ketone structural units. This special structural characteristic gives it excellent high and low temperature resistance, excellent mechanical properties, dimensional stability, medium resistance, weather resistance, flame retardancy and nuclear radiation resistance, etc. It is particularly suitable for the matrix resin of high-performance thermoplastic composite materials and super engineering plastics. It has a wide range of applications in high-tech fields such as aerospace, microelectronics, information engineering, mechanical equipment manufacturing, medical equipment, oil extraction, transportation and weapon equipment, and has become one of the indispensable new materials in modern high-tech fields.

[0003] There are two technical routes for the preparation of PEAK. One is the nucleophilic route, that is, a nucleophilic substitution reaction occurs between a ketone-containing difluoro monomer and a bisphenol (sodium, potassium) salt monomer in a high-boiling point non-protonic, highly polar organic solution to form an ether bond that connects the aromatic ring skeleton into a linear polymer. The most typical examples are polyaryletheretherketone (PEEK), polyaryletherketone (PEK) and PEEKK. The other method is called the electrophilic route, that is, a ketone group is formed by a Friedel-Crafts acylation reaction between aromatic diacyl chloride and aromatic ether in the presence of anhydrous aluminum chloride catalyst to connect the aromatic ring skeleton into a linear macromolecule. It can be seen that the type, structure and purity of the monomer determine the structure, type and performance of the polymer.

[0004] PEAK is mostly a crystalline polymer. It is insoluble in common organic solvents except for a few strong protic acids such as concentrated H2SO4. Moreover, its melting temperature (T m ) is relatively high, and the glass transition temperature (T g ) is relatively low. For example, the T m 343℃, T g The T of PEKK is 143°C. m 354℃, T g The melting temperature of PEAK resin is generally 30℃ to 60℃ higher than its Tm, which places high demands on processing equipment and processes. There are many difficulties in processing and molding, which limits its application range. Therefore, the glass transition temperature (T g ), appropriately lowering its melting temperature (Tm) to basically maintain its high and low temperature resistance, as well as its solubility in some common low-toxic organic solvents, and being able to be processed and molded by solvent method is one of the hot topics in the research and development of polyaryletherketone.

[0005] Hyperbranched poly(aryletherketone) (HBPEAK) not only has the excellent mechanical properties of linear poly(aryletherketone) resin, but also has the unique melt fluidity of hyperbranched polymers, high T g and lower T m , the melt processing performance is significantly improved.

[0006] Patent application CN 107987272A uses 1,3,5-benzene trimethylene chloride, 1,2,4-benzene trimethylene chloride, di-(3,4-phthalic anhydride) benzophenone as branching agents, adopts an electrophilic polymerization route, and co-condenses with TPC, IPC, and diphenyl ether (DPE) to synthesize a high molecular weight polyaryletherketone. This method uses benzene trimethylene chloride, di-(3,4-phthalic anhydride) benzophenone as branching agents to synthesize hyperbranched PEKK. Although a high molecular weight polymer can be obtained, the branching agent is unstable and easily hygroscopic and deteriorates. It causes side reactions under Friedel-Crafts acylation polycondensation reaction conditions, and the obtained HBPEKK has insufficient melt thermal oxidation stability.

[0007] Therefore, there is an urgent need for a polyaryletherketone having a high glass transition temperature, a low melting temperature, good high and low temperature resistance, good solubility in common low-toxic organic solvents, and good melt thermal oxidation stability, and a preparation method thereof. Summary of the invention

[0008] To solve the above problems, the present invention provides the following technical solutions.

[0009] In a first aspect, a polyaryletherketone resin is provided.

[0010] A polyaryletherketone resin having a structure as shown in formula I,

[0011]

[0012] Wherein, A2 is an aromatic diacyl structure;

[0013] B2 is an aromatic ether structure;

[0014] B3 is selected from:

[0015]

[0016] m, n, and p are the degrees of polymerization;

[0017] The aromatic diacyl structure is

[0018]

[0019] The aromatic ether structure is:

[0020] and selected from

[0021]

[0022]

[0023] One of them.

[0024] The polyaryletherketone resin is a star-shaped polyaryletherketone resin.

[0025] In some embodiments, the polyaryletherketone resin has an inherent viscosity of 0.50 g / dl-1.25 g / dl.

[0026] In some embodiments, the aromatic diacyl structure is

[0027]

[0028] The aromatic ether structure is:

[0029] and selected from

[0030]

[0031] One of the above; in such embodiments, the obtained polyaryletherketone resin is referred to as ST-PEKKS-TH resin.

[0032] In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.50 g / dl-1.25 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.60 g / dl-1.26 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.68 g / dl-1.26 g / dl.

[0033] In a second aspect, a method for preparing a polyaryletherketone resin is provided.

[0034] A method for preparing a polyaryletherketone resin comprises: reacting s-triphenyloxybenzene, arylether and aromatic dichloride in a catalyst solvent system, and performing post-treatment to obtain the polyaryletherketone resin.

[0035] In some embodiments, a method for preparing the polyaryletherketone resin of the first aspect comprises: mixing an aromatic ether with a catalyst solvent system to undergo a complexation reaction, adding aromatic dichloride to undergo a Friedel-Crafts acylation reaction, then adding triphenoxybenzene to undergo a first reaction, and obtaining the polyaryletherketone resin through post-treatment.

[0036] In some embodiments, the structure of the polyaryletherketone resin is as shown in the structure of the polyaryletherketone resin shown in Formula I described in the first aspect.

[0037] In some embodiments, the polyaryletherketone resin has an inherent viscosity of 0.50 g / dl-1.25 g / dl.

[0038] In some embodiments, the aromatic dicarboxylic acid chloride is

[0039] The aromatic ether is:

[0040] and selected from

[0041]

[0042] One of the above; in this embodiment, the obtained polyaryletherketone resin is ST-PEKKS-TH resin.

[0043] In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.50 g / dl-1.25 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.60 g / dl-1.26 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.68 g / dl-1.26 g / dl.

[0044] In some embodiments, the molar ratio of triphenoxybenzene to aromatic ether in the aforementioned ST-PEKKS-TH resin is (1.00-1.50):100.00.

[0045] In some embodiments, the molar ratio of the aromatic ether to the aromatic diacyl chloride in the aforementioned ST-PEKKS-TH resin is (1.00-1.05):1.00.

[0046] In some embodiments, the catalyst solvent system includes a diluent, a Lewis acid, a Lewis base, and a co-catalyst.

[0047] In some embodiments, the diluent comprises an aprotic organic solvent.

[0048] In some embodiments, the aprotic organic solvent includes one or more of dichloromethane (DCM), dichloroethane (DCE), chloroform, o-dichlorobenzene, and tetrachloroethane.

[0049] In some embodiments, the aprotic organic solvent includes one or more of dichloromethane, dichloroethane, and o-dichlorobenzene. In some embodiments, 0.10 mol to 0.80 mol of aromatic dichloride is added per 1 L of the diluent. In some embodiments, 0.30 mol to 0.70 mol of aromatic dichloride is added per 1 L of the diluent.

[0050] In some embodiments, the Lewis acid comprises one or more of AlCl 3 , FeCl 3 , and InCl 3 . In some preferred embodiments, the Lewis acid is AlCl 3 .

[0051] In some embodiments, the molar amount of the Lewis acid is the total molar amount of the carbonyl, keto, amide and sulfone groups in the feed in the complex reaction, plus the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction, and the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction is 0.5 to 2.2 times the molar amount of the aromatic diacyl chloride. In some embodiments, the molar amount of the Lewis acid is the total molar amount of the carbonyl, keto, amide and sulfone groups in the feed in the complex reaction, plus the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction, and the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction is 0.5 to 1.0 times the molar amount of the aromatic diacyl chloride.

[0052] In some embodiments, the Lewis base includes one or more of NN-dimethylformamide (DMF), NN-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), sulfolane and diphenyl sulfone.

[0053] In some embodiments, the co-catalyst includes an organic acid salt or an inorganic acid salt.

[0054] In some embodiments, the promoter comprises Fe 2+ Halogen salt, Cu +1 Halogen salt, Sn 2+ One or more of halides, phosphates, phosphites, formates, acetates, and oxalates.

[0055] In some preferred embodiments, the co-catalyst includes one or more of CuBr and Cu2PO3.

[0056] In some embodiments, the halide salt is a fluoride salt, a chloride salt, a bromide salt or an iodide salt. In some preferred embodiments, the halide salt is a chloride salt or a bromide salt.

[0057] In some embodiments, the mass ratio of the co-catalyst to the Lewis acid is 0.1:100.0 to 1.0:100.0 or 0.1:100.0 to 0.8:100.0. In some embodiments, the mass ratio of the co-catalyst to the Lewis acid is 0.1:100.0, 0.2:100.0, 0.3:100.0, 0.4:100.0, 0.5:100.0, 0.6:100.0, 0.7:100.0 or 0.8:100.0.

[0058] In some embodiments, the reaction temperature of the complexation reaction is 10°C to 28°C.

[0059] In some embodiments, the reaction temperature of the Friedel-Crafts acylation reaction is -15°C to 5°C.

[0060] In some embodiments, the reaction temperature of the first reaction is 0°C to 25°C.

[0061] In some embodiments, the reaction time of the first reaction is 30 minutes to 60 minutes.

[0062] In some embodiments, the reaction time of the first reaction is 4 hours to 6 hours.

[0063] In some embodiments, the post-treatment includes: adding crushed ice to quench the reaction, precipitating the polymer, standing and separating the layers, removing the water layer, washing the precipitate with water, evaporating the diluent, crushing the precipitate in an alcohol solution or water, filtering, washing with water, and drying to obtain the polyaryletherketone resin.

[0064] In some embodiments, the alcohol solution is a methanol aqueous solution with a concentration of 95% vol and above or an ethanol aqueous solution with a concentration of 95% vol and above.

[0065] In a third aspect, the present invention provides another method for preparing polyaryletherketone resin.

[0066] In some embodiments, a method for preparing a polyaryletherketone resin comprises: mixing an aromatic ether component 1 with a catalyst solvent system to generate a complex reaction, wherein the aromatic ether component 1 is DPODPS and / or p-EKKE; then adding aromatic dichloride to perform a Friedel-Crafts acylation reaction, then adding triphenoxybenzene (B3) to perform a second reaction, and then adding an aromatic ether component 2 to perform a third reaction, wherein the aromatic ether component 2 is DPE; and after post-treatment, the polyaryletherketone resin is obtained, and the obtained polyaryletherketone resin is ST-PEKKS-TH resin.

[0067] In some embodiments, a method for preparing a polyaryletherketone resin comprises: mixing an arylether component 1 with a catalyst solvent system to generate a complexation reaction, wherein the arylether component 1 is DPODPS and / or p-EKKE; then adding aromatic diacyl chloride to perform a Friedel-Crafts acylation reaction, then adding triphenoxybenzene to perform a second reaction, and then adding an arylether component 2 to perform a third reaction, wherein the arylether component 2 is DPE; and after post-treatment, obtaining the polyaryletherketone resin, wherein the aromatic diacyl chloride is The obtained polyaryletherketone resin is ST-PEKKS-TH resin.

[0068] In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.50 g / dl-1.25 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.60 g / dl-1.26 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKKS-TH resin is 0.68 g / dl-1.26 g / dl. In some embodiments, the logarithmic inherent viscosity of the aforementioned ST-PEKK resin is 0.60 g / dl to 0.85 g / dl, preferably 0.65 g / dl to 0.85 g / dl.

[0069] In some embodiments, the ratio of the total molar amount of the aromatic ether component 1 and the aromatic ether component 2 to the molar amount of triphenoxybenzene (B3) is 100.00:(1.00-1.50).

[0070] In some embodiments, the ratio of the total molar amount of the aromatic ether component 1 and the aromatic ether component 2 to the molar amount of the aromatic dicarboxylic acid chloride (A2) is (1.00-1.05):1.00.

[0071] In some embodiments, the molar ratio of the aromatic ether component 1 to the aromatic ether component 2 is (4-7):(6-3). In some embodiments, the molar ratio of the aromatic ether component 1 to the aromatic ether component 2 is 4:6-7:3.

[0072] In some embodiments, the catalyst solvent system includes a diluent, a Lewis acid, a Lewis base, and a co-catalyst.

[0073] In some embodiments, the diluent comprises an aprotic organic solvent.

[0074] In some embodiments, the aprotic organic solvent includes one or more of dichloromethane (DCM), dichloroethane (DCE), chloroform, o-dichlorobenzene, and tetrachloroethane.

[0075] In some embodiments, the aprotic organic solvent includes one or more of dichloromethane, dichloroethane, and o-dichlorobenzene.

[0076] In some embodiments, 0.10 mol to 0.80 mol of aromatic dicarboxylic acid chloride is added to every 1 L of the diluent.

[0077] In some embodiments, 0.30 mol to 0.70 mol of aromatic dicarboxylic acid chloride is added to every 1 L of the diluent.

[0078] In some embodiments, the Lewis acid comprises one or more of AlCl 3 , FeCl 3 , and InCl 3 . In some preferred embodiments, the Lewis acid is AlCl 3 .

[0079] In some embodiments, the molar amount of the Lewis acid is the total molar amount of the carbonyl, keto, amide and sulfone groups in the feed in the complex reaction, plus the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction, and the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction is 0.5 to 2.2 times the molar amount of the aromatic diacyl chloride. In some embodiments, the molar amount of the Lewis acid is the total molar amount of the carbonyl, keto, amide and sulfone groups in the feed in the complex reaction, plus the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction, and the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction is 0.5 to 1.0 times the molar amount of the aromatic diacyl chloride.

[0080] In some embodiments, the Lewis base includes one or more of NN-dimethylformamide (DMF), NN-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), sulfolane and diphenyl sulfone.

[0081] In some embodiments, the molar ratio of the Lewis base to the aromatic diacyl chloride is (0.10-2.50):1.00. In some embodiments, the molar ratio of the Lewis base to the aromatic diacyl chloride is (0.20-2.00):1.00.

[0082] In some embodiments, the co-catalyst includes an organic acid salt or an inorganic acid salt.

[0083] In some embodiments, the promoter includes Fe 2+ Halogen salt, Cu +1 Halogen salt, Sn 2+ One or more of halides, phosphates, phosphites, formates, acetates, and oxalates.

[0084] In some preferred embodiments, the co-catalyst includes one or more of CuBr, CuCl, and Cu2PO3.

[0085] In some embodiments, the halide salt is a fluoride salt, a chloride salt, a bromide salt or an iodide salt. In some preferred embodiments, the halide salt is a chloride salt or a bromide salt.

[0086] In some embodiments, the mass ratio of the co-catalyst to the Lewis acid is 0.1:100.0 to 1.0:100.0 or 0.1:100.0 to 0.8:100.0. In some embodiments, the mass ratio of the co-catalyst to the Lewis acid is 0.1:100.0, 0.2:100.0, 0.3:100.0, 0.4:100.0, 0.5:100.0, 0.6:100.0, 0.7:100.0 or 0.8:100.0.

[0087] In some embodiments, the reaction temperature of the complexation reaction is 10°C to 28°C.

[0088] In some embodiments, the reaction temperature of the Friedel-Crafts acylation reaction is -15°C to 5°C.

[0089] In some embodiments, the reaction temperature of the second reaction is 0°C to 25°C.

[0090] In some embodiments, the reaction temperature of the third reaction is 0°C to 25°C, preferably 15°C to 25°C.

[0091] In some embodiments, the post-treatment includes: adding crushed ice to quench the reaction, precipitating the polymer, standing and separating the layers, removing the water layer, washing the precipitate with water, evaporating the diluent, crushing the precipitate in an alcohol solution or water, filtering, washing with water, and drying to obtain the polyaryletherketone resin.

[0092] In some embodiments, the alcohol solution is a methanol aqueous solution with a concentration of 95% vol and above or an ethanol aqueous solution with a concentration of 95% vol and above.

[0093] In a fourth aspect, there is provided a use of the polyaryletherketone resin of the first aspect, the polyaryletherketone resin obtained by the preparation method of the second aspect, or the polyaryletherketone resin obtained by the preparation method of the third aspect.

[0094] A use of the polyaryletherketone resin of the first aspect, the polyaryletherketone resin obtained by the preparation method of the second aspect, or the polyaryletherketone resin obtained by the preparation method of the third aspect in preparing a polyaryletherketone resin-based prepreg for fiber fabric or a polyaryletherketone resin-based composite material for fiber fabric.

[0095] In a fifth aspect, a polyaryletherketone resin-based prepreg for a fiber fabric is provided.

[0096] A polyaryletherketone resin-based prepreg for fiber fabric, comprising: fiber fabric and at least one polyaryletherketone resin selected from the polyaryletherketone resin described in the first aspect, the polyaryletherketone resin obtained by the preparation method described in the second aspect, or the polyaryletherketone resin obtained by the preparation method described in the third aspect.

[0097] In some embodiments, the fiber fabric includes any one of carbon fiber, glass fiber, basalt fiber, boron nitride fiber, carbon nanotube fiber, graphene fiber, aramid fiber, polybenzoxazole (PBO), and polybenzimidazole (PBI).

[0098] In some embodiments, the fiber fabric is in the shape of any one of plain fabric, twill fabric, satin fabric, three-dimensional woven fabric or unidirectional fiber.

[0099] In a sixth aspect, a polyaryletherketone resin-based composite material of a fiber fabric is provided.

[0100] A polyaryletherketone resin-based composite material for fiber fabrics is prepared by subjecting the polyaryletherketone resin-based prepreg for fiber fabrics described in the fifth aspect to melting, hot pressing, cooling and solidification.

[0101] Beneficial Effects

[0102] An embodiment provided by the present invention has at least one of the following beneficial effects:

[0103] (1) The present invention uses homemade 1.3.5-triphenoxybenzene (TPOB) as the "core" monomer B3, which has a symmetrical structure and stable properties, does not absorb water and deteriorate, and is easy to store. It can be co-condensed with DPODPS, DPE, 1,4- or 1,3-di(4-phenoxybenzoyl)benzene (P-EKKE or m-EKKE), 1,4-diphenoxybenzene, 1,3-diphenoxybenzene, 4,4'-diphenoxybenzophenone and other B2 monomers under Friedel-Crafts acylation reaction conditions and aromatic diacyl chloride A2 to prepare soluble and melt-type star-shaped polyaryletherketoneketone (ST-PEKK), star-shaped polyaryletherketoneketonesulfone (ST-PEKKS) and other thermoplastic resin varieties with different properties;

[0104] (2) Controlling polymer molecular weight, melt thermal oxidation stability, and thermal properties of the resin by adding TPOB in molar mass and method;

[0105] (3) The separation and purification method of the prepared polyaryletherketone resin is simple, and the diluent DCM can be recycled and reused after distillation and constant boiling dehydration, which is beneficial to energy conservation, emission reduction and environmental protection;

[0106] (4) The resin is crushed in a wet state, which avoids the pollution of the production environment by the resin dust in the dry state;

[0107] (5) The HCl gas released by the polycondensation reaction is absorbed by water and converted into dilute hydrochloric acid byproduct;

[0108] (6) The prepared star-shaped PEAK and carbon fiber (CF) and other reinforcing materials have good interface wettability and can be made into carbon fiber composite prepreg by solvent method, slurry method, electrostatic powder impregnation method and melt impregnation method. After hot pressing, high-strength and high-modulus composite materials can be obtained. They have broad application prospects in aerospace, aviation, weapon equipment and civil high-tech fields.

[0109] (7) The polyaryletherketone resin provided by the present invention or the polyaryletherketone resin obtained by the preparation method provided by the present invention has the advantages of high glass transition temperature, low melting temperature, good high and low temperature resistance, good solubility in common low-toxic organic solvents, and good melt thermal oxidation stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0110] Figure 1 This is the DSC (differential scanning calorimetry) secondary temperature rise curve of the ST-PEKKS-TM resin obtained in Example 1.

[0111] Figure 2 The DSC (differential scanning calorimetry) curve of the ST-PEKKS-TM resin obtained in Example 1 is shown in FIG.

[0112] Figure 3 This is the TG-DTG (thermogravimetric analysis) curve of the ST-PEKKS-TM resin obtained in Example 1.

[0113] Figure 4 This is the DSC (differential scanning calorimetry) secondary temperature rise curve of the ST-PEKKS-TS resin obtained in Example 9.

[0114] Figure 5 This is the DSC (differential scanning calorimetry) curve of the ST-PEKKS-TS resin obtained in Example 9.

[0115] Figure 6 This is the TG-DTG (thermogravimetric analysis) curve of the ST-PEKKS-TS resin obtained in Example 9.

[0116] Figure 7 This is the TG-DTG (thermogravimetric analysis) curve of the TS-PEKKS resin obtained in Example 18.

[0117] Figure 8 This is the DSC (differential scanning calorimetry) secondary temperature rise curve of the TS-PEKKS resin obtained in Example 18.

[0118] Fig. 9 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 39.

[0119] Fig.10This is the TG (thermogravimetric analysis) curve of the ST-PEKK resin obtained in Example 39.

[0120] Fig.11 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 40.

[0121] Fig.12 This is the TG (thermogravimetric analysis) curve of the ST-PEKK resin obtained in Example 40.

[0122] Fig.13 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 42.

[0123] Fig.14 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 43.

[0124] Fig.15 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 44.

[0125] Fig.16 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 45.

[0126] Fig.17 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 46.

[0127] Fig.18 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 47.

[0128] Fig.19 This is the DSC (differential scanning calorimetry) curve of the ST-PEKK resin obtained in Example 48.

[0129] Definition of terms

[0130] In the above text of the present invention, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. Based on the disclosed numbers, the value of each number may vary by less than ±10% or reasonable differences considered by those skilled in the art, such as ±1%, ±2%, ±3%, ±4% or ±5%.

[0131] The terms "above", "below", "within" and the like are understood to include the number itself, for example, more than two means ≥ two.

[0132] The term "and / or" should be understood to mean any one of the optional items or a combination of any two or more of the optional items.

[0133] The term "% vol" means volume percentage.

[0134] "Prepreg" refers to a storable composition of a resin matrix and a reinforcement made by impregnating continuous fibers or fabrics with a resin matrix under certain conditions.

[0135] The term "plurality" means a number of 2 or more, for example, 2, 3, 4 or 5, etc.

[0136] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction. DETAILED DESCRIPTION

[0137] In order to enable those skilled in the art to better understand the technical solution of the present invention, some non-limiting embodiments are further disclosed below to further illustrate the present invention in detail.

[0138] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.

[0139] The logarithmic relative viscosity of the resin (η inh ) Determination: Prepare the resin into a 0.5g / dL concentrated sulfuric acid solution and measure it in a constant temperature water bath at 30℃±0.5℃. According to the formula η inh =C -1 ln(t1 / t0); where C is the concentration of the resin in concentrated sulfuric acid (g / dL), t0 and t1 are the time that the solvent concentrated sulfuric acid and the resin concentrated sulfuric acid solution flow through the capillary of the Ubbelohde viscometer, respectively, in seconds; Thermal oxidation stability test: refer to the method for evaluating the thermal oxidation stability of PEKK in WO840389, take 2g of resin powder and place it on a stainless steel disc with a high temperature thermometer, heat it to 300-360℃ to melt, take samples at regular intervals, and measure η in the air inh Change (△η inh ) and observe the time (min) for which the resin maintains a good flow state.

[0140] Glass transition temperature (T g ) or melting temperature (T m) Detection method: Differential scanning calorimetry (DSC) was used to determine the T g or T m , a NETZSCHDSC214 differential scanning calorimeter was used, the heating and cooling rate was 10K / min, the test temperature range was 50~400℃, and the atmosphere was nitrogen.

[0141] Thermal decomposition temperature (T d ) Detection method: Thermogravimetric analysis (TGA) was performed using a NETZSCHTG 209F thermogravimetric analysis to determine the thermal decomposition temperature (T d ), the test temperature range is 20~800℃, and the heating rate is 20K / min.

[0142] Solubility test method:

[0143] Weigh 2g of dry resin and place it in a 25mL white volumetric flask, add about 10mL of solvent, place it in a 30℃ constant temperature water bath for 3 to 6 hours, shake the volumetric flask, then add the same solvent to the scale, shake well and let it stand, and observe the changes in the physical state of the resin.

[0144] a. Dissolved (+): The solute and solvent are homogeneous and transparent.

[0145] b. Swelling (+-): The solute and solvent are turbid and opaque, and swollen resin particles can be observed.

[0146] c. Insoluble (-): the solute and solvent are clearly separated into layers.

[0147] Main ingredients:

[0148] 1,3,5-Triphenoxybenzene (TPOB), homemade, MP: 112℃~113℃, (thermometer uncalibrated), structure determined by mass spectrometry and 1 HNMR analysis and characterization;

[0149] 4,4′-diphenoxydiphenyl sulfone (DPODPS), homemade, MP: 139℃~141℃, structure by mass spectrometry, 1 HNMR characterization;

[0150] TPC, IPC, anhydrous AlCl3, DCM, DCE, etc. are all industrial products and are used directly without treatment. DPE industrial products are used after purification by vacuum distillation.

[0151] 1,4-Di(4-phenoxybenzoyl)benzene (p-EKKE), MP: 217℃; 1,3-Di(4-phenoxybenzoyl) (m-EKKE), MP: 122℃; prepared with reference to “Synthesis and Characterization of 1,4-Di(4-phenoxybenzoyl)benzene” (Journal of Jiangxi Normal University (Natural Science Edition) 31(5) 519-522, 2007) and “Study on the Effect of Different Monomers on the Structure and Properties of Synthesized Polyaryletherketoneketone (PEKK)” (Acta Polymerica Sinica 2008, 10, 1016-1019).

[0152] The abbreviations of the compounds in the context of the present invention and their corresponding structures are:

[0153]

[0154]

[0155] Examples 1 to 8 (Preparation of ST-PEKKS-TM), Comparative Example 1:

[0156] Monomer: TPOB (B3), DPODPS (B2), TPC (A2)

[0157] Step A:

[0158] a) AlCl3 (76 g, 0.57 mol) and a co-catalyst CuBr (0.3 g) were mixed with DCM (150 ml), stirred, cooled to 0°C to 5°C, and a mixture of DMF (the amount of DMF added in each embodiment and reference example is shown in Table 1, wherein the molar amount of 15 ml of DMF is 0.205 mol) and DCM (30 ml) was added. The complex reaction was exothermic, and when the temperature rose to about 25°C, DPODPS (the amount of DPODPS added in each embodiment and reference example is shown in Table 1) was added and stirred to dissolve, thereby obtaining a reaction mixture 1;

[0159] b) Cool the reaction mixture 1 to -10°C ± 5°C, add TPC (the amount of TPC added in each embodiment and control example is shown in Table 1), stir and react at -5°C ± 5°C for 30 min to 60 min, add TPOB (the amount of TPOB added in each embodiment and control example is shown in Table 1), raise the temperature to 20°C ± 5°C and continue stirring and reacting for 4 to 5 h;

[0160] c) Add 400 ml of ice water to quench the reaction, stir to precipitate white granular resin, let it stand for stratification, wash the resin layer with deionized water, distill and recover DCM, filter, and crush the filtered resin in 95% ethanol for several times, filter, wash with water, and dry to obtain ST-PEKKS resin (white fine granules). Detect the logarithmic specific viscosity (η inh ), glass transition temperature (T g), melting temperature (T m ), thermal decomposition temperature (T d ) and solubility. The results are shown in Table 1.

[0161] The structural formula of ST-PEKKS-TM:

[0162]

[0163] Table 1: Preparation and thermal performance test results of ST-PEKKS-TM

[0164]

[0165] Note: Tg is the value of the second temperature rise curve of DSC. Tg has the same meaning in the following text.

[0166] In the solubility, “-” means insolubility; “+-” means swelling; “+” means dissolution. The symbols below have the same meaning.

[0167] Conclusion: The Tg of the copolymer increased by more than 4°C and the Tm decreased by 15°C, which is beneficial to reducing the melt processing temperature of the resin.

[0168] Examples 9 to 12 (Preparation of ST-PEKKS-TS resin), Comparative Example 2:

[0169] The A2 monomer TPC in the preparation method of Examples 1 to 8 is replaced by TPC and / or IPC, the types of the other monomers and reagents are the same as in Examples 1 to 8, and each monomer and Lewis base is fed in the amount shown in Table 2, and the preparation is carried out according to the preparation method of Examples 1 to 8 to obtain ST-PEKKS-TS resin. The logarithmic reduced viscosity (η inh ), glass transition temperature (T g ), melting temperature (T m ), thermal decomposition temperature (T d ) and solubility. The results are shown in Table 2.

[0170] Table 2: Preparation and thermal properties test results of ST-PEKKS-TS

[0171]

[0172] in conclusion:

[0173] In Table 2, “*” indicates that no crystal melting peak was observed on the second DSC temperature rise curve.

[0174] Compared with Example 12, the Tg of Example 11 is increased by 10°C and the Tm is close; compared with Control Example 2, the Tg of Example 11 is 9°C higher. The experiment shows that when DPODPS and TPC / IPC are co-condensed and the molar ratio of TPC to IPC is less than 0.60:0.40, the polymer is transformed into an amorphous structure.

[0175] ST-PEKKS-TS is in a slightly crystalline aggregate state, which is conducive to its dissolution in solvents such as DMF, NMP or halogenated hydrocarbons, and is conducive to its use of a wet method to compound with reinforcing materials to form composite material prepregs.

[0176] Examples 13-31: Preparation of TS-PEKKS resin

[0177] Preparation method: The molar mass ratio of the monomers in Examples 13 to 31 is the same as that in Example 9, and ST-PEKKS-TS copolymers with different ηinh are prepared by referring to operation step A. Thermal oxidative stability test: The TS-PEKKS resins obtained in Examples 13 to 18 are taken to test the initial η inh The η values ​​were measured at different time points after being placed at 330℃±10℃ for 0.5h, 1h, 2h, and 3h. inh The results are shown in Table 3.

[0178] Melt index: Referring to the national standard method (GB3682-2000), a melt flow rate tester was used to test Examples 19-24. The results are listed in Table 4.

[0179] Mechanical properties of TS-PEKKS-TS / CF (cloth) composite laminate: Two commercially available carbon fiber fabrics and TS-PEKKS-TS resin obtained in Examples 25 to 31 were used to prepare prepreg (Examples 25-31 are soluble TS-PEKKS with different ηinh, and the monomer molar ratio is the same as that in Example 9), and programmed temperature rise hot pressing was used to prepare laminates to obtain TS-PEKKS-TS / CF (cloth) composite laminates, which were cut into standard specimens and tested for mechanical properties according to the GB-T1447-2005 method. The mechanical properties test results of TS-PEKKS-TS / CF (cloth) composite laminates are listed in Table 5.

[0180] Table 3: Thermo-oxidative stability of TS-PEKKS resin

[0181]

[0182] Table 4: Melt Index of TS-PEKKS Resins*

[0183]

[0184] *Instrument name: Melt flow rate testing machine

[0185] Conclusion: It can be seen from Tables 3 and 4 that the TS-PEKKS resin provided by the present invention has excellent thermal oxidation stability, and the melt fluidity and molecular weight (η inh ) is inversely proportional to the η of TS-PEKKS resin, which is the matrix resin of carbon fiber (CF) composite materials. inh Preferably it is 0.65±0.05 g / dl.

[0186] Table 5: Mechanical properties of TS-PEKKS-TS / CF (cloth) composite laminates

[0187]

[0188]

[0189] Conclusion: The soluble TS-PEKKS resin prepared by the present invention has a higher glass transition temperature (Tg) and a lower melting transition temperature (Tm), a lower melt viscosity, good thermal stability, good wettability with carbon fiber T3003K (cloth) T70012K (cloth), can be made into prepreg by wet impregnation, and can be made into high-strength, high-modulus ST-PEKKS / CF (cloth) composite material structural parts after hot pressing. It has broad application prospects in aviation, aerospace, military equipment and high-end civilian fields.

[0190] Examples 32 to 38: Preparation of ST-PEKKS-TH resin (TH represents high temperature resistant type)

[0191] Monomer: B3:TPOB, B2:DPODPS, DPE or p-EKKE, A2:TPC

[0192] Implementation Step B:

[0193] AlCl3 (72-85 g) was mixed with DCM (150-180 ml), and a DCM mixture of DMF (or NMP) (Lewis base, the amount added is shown in Table 6) was added, and the temperature was controlled below 25°C. DPODPS and p-EKKE in the B2 monomer were added, wherein p-EKKE and DPODPS formed a complex with aluminum chloride, and the DPODPS and p-EKKE were completely dissolved into a transparent state by stirring. The mixture was cooled to -10°C±5°C, and the A2 monomer was added. The mixture was reacted at -5°C to 5°C for 30 min to 1 h. The B3 monomer was added. The mixture was reacted at 5°C to 10°C for 1 h to 2 h, at 15°C±5°C for 2 h, and then at 20°C±5°C for 1 h. The preparation of the resins of Control Example 3, Example 32, Example 33, and Example 34 also included the addition of DPE for 1 h. The reaction was quenched with cold water or methanol or 95% ethanol aqueous solution. After solid-liquid separation, the resin was crushed several times in 95% ethanol, washed with water, and dried to obtain ST-PEKKS-TH resin. The logarithmic specific viscosity (η inh ), glass transition temperature (T g ), melting temperature (T m ) and thermal decomposition temperature (T d ), the results are shown in Table 6.

[0194] Table 6: Preparation of ST-PEKKS-TH

[0195]

[0196]

[0197] "*" in Table 6: As the molar content of diphenoxydiphenyl sulfone structural unit (DPODPS) in the terpolymer molecular chain increases (for example, the proportions in Examples 35 and 36), the glass transition temperature (Tg) increases and the crystalline melting temperature (Tm) decreases. However, when the molar content of diphenoxydiphenyl sulfone structural unit (DPODPS) is high to a certain extent (for example, the proportion in Example 38), it is difficult to measure the crystalline melting peak (Tm) on the DSC temperature rise curve.

[0198] Conclusion: Examples 32 to 38 are terpolymers containing star-shaped structural units. Compared with PEKK (Tg: 156°C, Tm: 356°C), ST-PEKKS-TH has a higher Tg than PEKKS-TH. g There is a significant improvement, T m 、T d Equivalent to PEKK.

[0199] Examples 39-48: Preparation of ST-PEKK resin

[0200] Monomer: B3: TPOB; B2: at least one of DPE, p-EKKE, m-EKKE, etc.; A2: TPC and / or IPC.

[0201] Implementation Step C:

[0202] a. Mix anhydrous aluminum chloride (the amount of anhydrous aluminum chloride is calculated as follows: ① the amount of anhydrous aluminum chloride used in the complex reaction: the amount of anhydrous aluminum chloride required for the formation of a complex with carbonyl groups, amide groups, etc. in the reaction system at a molar ratio of 1.0:1.0 + ② the amount of anhydrous aluminum chloride used in the acylation reaction: 0.5 to 1.2 times the molar amount of aromatic diacyl chloride added) and a co-catalyst CuBr (0.3 g) with DCM (150 to 180 ml), add a mixed solution of a Lewis base DMF, DMAc or NMP and a diluent DCM at 10°C ± 5°C, and the molar amount of the Lewis base added is 0.5 to 1.2 times the molar amount of aromatic diacyl chloride added. The molar amount is 0.2 times the molar amount of aromatic diacyl chloride, and then monomer B2 (DPE, p-EKKE and / or m-EKKE, the type and amount of addition are shown in Table 7) is added, aluminum chloride and monomer B2 undergo complexation reaction, and stirred to obtain reaction mixture 1; the reaction mixture 1 is cooled to -15℃±5℃, A2 monomer (TPC and / or IPC, the type and amount of addition are shown in Table 7) is added, and the reaction is carried out for 30min~1h, the temperature is raised to 5℃~15℃, and then B3 monomer TPOB (the amount of addition is shown in Table 7) is added, and the polycondensation reaction is continued at 15℃~25℃ for 5~6h. The molar concentration of the monomer is controlled at 0.2-0.6mol / L (the molar concentration of the monomer refers to the molar concentration of all monomers (A2+B2+B3) in the diluted DCM plus Lewis base, and can be changed and adjusted accordingly according to the implementation of the polycondensation reaction).

[0203] b. Quenching reaction

[0204] After the polycondensation reaction is completed, 300ml to 500ml of ice water is added to decompose the complex formed by ST-PEKK and AlCl3, and the complex is dissolved and stirred to obtain a white fine granular resin, which is heated to 50°C ± 5°C to evaporate DCM, and the solid-liquid separation is performed to obtain ST-PEKK resin (white). The ST-PEKK resin is crushed several times in 95% ethanol or methanol, and then washed with water to the washing liquid, and the washing liquid is tested for chloride ions with silver nitrate ammonia solution, and dried to obtain a refined ST-PEKK resin. The melt thermal stability of the ST-PEKK resin obtained in Example 47 and Example 48 at 360°C-380°C is tested, and the results are shown in Table 8.

[0205] Table 7: Preparation and thermal properties of ST-PEKK

[0206]

[0207] In Table 7, “*” indicates a powder sample.

[0208] In Table 7, "**" indicates a sample after melting.

[0209] The thermal properties of ST-PEKK are closely related to its thermal history. Samples 45* and 46* are unmelted ST-PEKK powders.

[0210] The second DSC heating curve measured that 45*Tg was 163.9~165.3℃, Tm was 362.8℃, 46*Tg was 154.1~169.7℃, and cold crystallization peaks (Tc) appeared at 294.8℃ and 297.6℃ on the DSC cooling curve; 42** and other samples were melted samples, and there was a melting exothermic peak at about 200℃ on the DSC heating curve, followed by a crystallization melting peak.

[0211] Conclusion: The PEKK resin prepared by the pro-circuit route is prepared by using monomers such as DPE, TPC, and IPC. The biggest problem in preparing PEKK using DPE as the aromatic ether monomer is the insufficient melt thermal stability of the resin. The thermal properties (Tg, Tm, Td) of PEKK are closely related to the molar ratio of para-phenyl to meta-phenyl in the molecular chain. The higher the molar mass ratio of para-phenyl, the higher the Tg and Tm, but the corresponding increase in the melt processing temperature limits its practical application range. The molar ratio of para-phenyl to meta-phenyl in PEKK resins with practical application value is generally controlled by the molar feed ratio of TPC / IPC. The molar ratio of para-phenyl to meta-phenyl in PEKK with commercial value is generally 70-30 / 30-70.

[0212] In the present invention, p-EKKE and m-EKKE are used as B2 monomers, TPOB is used as B3 monomers, and TPC and IPC are used as A2 monomers to prepare ST-PEKK resin. The molar ratio of para-position to meta-position phenyl in ST-PEKK macromolecule is adjusted by adjusting the molar ratio of B2 and A2 monomers at the same time, so as to obtain ST-PEKK resin with expected thermal properties and molecular weight. By comparing the experimental results of Examples 39 and 40, the molar ratio of para-position to meta-position phenyl in the prepared ST-PEKK is 5 / 5, and their Tg, Tm and Td are also close. It is generally believed that the η of PEKK resin is 5 / 5. inh If the molecular weight is greater than 0.60 g / dl, it is a high molecular weight resin. inh As the value increases, the melt viscosity increases and the melt processing performance deteriorates. inh Generally controlled at 0.62~0.85g / dl, η inh PEKK with a value of 0.65 to 0.75 g / dl has a lower melt viscosity and is suitable as a matrix resin for high-performance composite materials.

[0213] As a high-performance thermoplastic polymer material, ST-PEKK resin is required to be as stable as possible at the melt processing temperature, without obvious oxidative crosslinking and degradation. Table 8 lists the melt thermal oxidation stability test results of PEKK and ST-PEKK resins prepared in Example 48 and Example 47 at 360-380°C. It can be seen from Table 8 that the melt thermal oxidation stability of ST-PEKK in Example 47 is better than that in Example 48.

[0214] Table 8: Melt thermal stability of ST-PEKK resin and PEKK resin at 360-380°C

[0215]

[0216] Table 9: Melt Flow Rate (MFR) of PEKK and ST-PEKK Resins*

[0217]

[0218] Melt index measurements show (see Table 9) that Example 47 has better melt flow than Example 48.

[0219] Example 49: Mechanical properties test of ST-PEKK / CF composite laminate

[0220] Two commercially available carbon fiber fabrics (T700-3K and T800-6K) and the ST-PEKK resin obtained in Example 39 were respectively used to prepare prepregs. The powdered resin was evenly coated on the surface of the CF (cloth). The resin ratio was 42% ± 3%. The laminate pressure was 12 MPa and the temperature was 360° C. to 380° C. to obtain ST-PEKK / CF composite laminates. Standard specimens were cut and their mechanical properties were tested according to GB / T1447-2005 and GB / T 9341-2008 methods. The average value of 5 specimens was taken. The mechanical property test results of the ST-PEKK / CF composite laminates are listed in Table 10.

[0221] Table 10: Mechanical properties test of ST-PEKK / CF composite laminate

[0222] ST-PEKK / T700-3K ST-PEKK / T800-6K Test Standards Tensile strength / MPa 754 847 GB / T 1447-2005 Tensile modulus / GPa 56.4 58 GB / T 1447-2005 Bending strength / MPa 837 975 GB / T 9341-2008 Flexural modulus / GPa 67.2 75.3 GB / T 9341-2008

[0223] Conclusion: The soluble ST-PEKK resin prepared by the present invention has a high glass transition temperature (Tg) and a low melting transition temperature (Tm), low melt viscosity, good thermal stability, good wettability with carbon fiber (such as T700-3K and T800-6K), can be made into prepreg by wet impregnation, and can be made into high-strength, high-modulus ST-PEKK / CF composite material structural parts after hot pressing. It has broad application prospects in aviation, aerospace, military equipment and high-end civilian fields.

[0224] The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein within the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.

Claims

1. A polyaryletherketone resin having a structure as shown in formula I, in, A2 is an aromatic diacyl structure; B2 is an aromatic ether structure; B3 is selected from: m, n, and p are the degrees of polymerization; The aromatic diacyl structure is The aromatic ether structure is: and selected from one of; and The polyaryletherketone resin has a logarithmic inherent viscosity of 0.50 g / dl-1.26 g / dl.

2. A method for preparing the polyaryletherketone resin according to claim 1, comprising: reacting s-triphenyloxybenzene, arylether and aromatic dichloride in a catalyst solvent system, and performing post-treatment to obtain the polyaryletherketone resin; The aromatic dicarboxylic acid chloride is The aromatic ether is: and selected from One of; The polyaryletherketone resin has a logarithmic inherent viscosity of 0.60 g / dl-1.26 g / dl; The molar ratio of the s-triphenoxybenzene to the aromatic ether is (1.00-1.50):100.00; The molar ratio of the aromatic ether to the aromatic diacyl chloride is (1.00-1.05):1.

00.

3. A method for preparing the polyaryletherketone resin according to claim 1, comprising: The aromatic ether is mixed with a catalyst solvent system to undergo a complexation reaction, aromatic diacyl chloride is added to undergo a Friedel-Crafts acylation reaction, and then s-triphenoxybenzene is added to undergo a first reaction, followed by post-treatment to obtain the polyaryletherketone resin; The aromatic dicarboxylic acid chloride is The aromatic ether is: and selected from One of; The polyaryletherketone resin has a logarithmic inherent viscosity of 0.60 g / dl-1.26 g / dl; The molar ratio of the s-triphenoxybenzene to the aromatic ether is (1.00-1.50):100.00; The molar ratio of the aromatic ether to the aromatic diacyl chloride is (1.00-1.05):1.

00.

4. A method for preparing the polyaryletherketone resin according to claim 1, comprising: The aromatic ether component is mixed with a catalyst solvent system to generate a complex reaction, wherein the aromatic ether component is DPODPS and p-EKKE; aromatic diacyl chloride is added to perform a Friedel-Crafts acylation reaction, and then s-triphenoxybenzene is added to perform a second reaction, and the polyaryletherketone resin is obtained through post-treatment; The DPODPS is The p-EKKE is The aromatic dicarboxylic acid chloride is 5. A method for preparing the polyaryletherketone resin according to claim 1, comprising: The aromatic ether component 1 is mixed with a catalyst solvent system to generate a complex reaction, wherein the aromatic ether component 1 is DPODPS and p-EKKE; aromatic diacyl chloride is added to perform a Friedel-Crafts acylation reaction, and then triphenoxybenzene is added to perform a second reaction, and then the aromatic ether component 2 is added to perform a third reaction, wherein the aromatic ether component 2 is DPE, and the polyaryletherketone resin is obtained after post-treatment; The ratio of the total molar amount of the aromatic ether component 1 and the aromatic ether component 2 to the molar amount of triphenoxybenzene is 100.00:(1.00-1.50); The ratio of the total molar amount of the aromatic ether component 1 and the aromatic ether component 2 to the molar amount of the aromatic diacyl chloride is (1.00-1.05): 1.00; The molar ratio of the aromatic ether component 1 to the aromatic ether component 2 is (4-7):(6-3); The DPODPS is The p-EKKE is The aromatic dicarboxylic acid chloride is The DPE is 6. The preparation method according to any one of claims 3 to 5, wherein the polyaryletherketone resin has a logarithmic inherent viscosity of 0.60 g / dl-1.26 g / dl; and / or The catalyst solvent system comprises a diluent, a Lewis acid, a Lewis base and a co-catalyst; and / or The diluent comprises an aprotic organic solvent; and / or The aprotic organic solvent includes one or more of dichloromethane, dichloroethane, and o-dichlorobenzene; and / or 0.30 mol to 0.70 mol of aromatic diacyl chloride is added to every 1 L of the diluent; and / or The Lewis acid is AlCl3; and / or The molar amount of the Lewis acid is the sum of the molar amounts of the keto group, amide group and sulfone group in the complex reaction, plus the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction, and the molar amount of the Lewis acid required for catalysis in the Friedel-Crafts acylation reaction is 0.5 to 2.2 times the molar amount of the aromatic diacyl chloride; and / or The Lewis base includes one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), sulfolane and diphenyl sulfone; and / or The molar ratio of the Lewis base to the aromatic diacyl chloride is (0.2-2.0):1.0; and / or The co-catalyst comprises an organic acid salt or an inorganic acid salt; and / or The promoter includes one or more of CuBr and CuCl; and / or The mass ratio of the co-catalyst to the Lewis acid is (0.1-0.8):100.0; and / or The reaction temperature of the complex reaction is 10°C to 28°C; and / or The reaction temperature of the Friedel-Crafts acylation reaction is -15°C ± 5°C, and / or; The reaction temperature of the first reaction or the second reaction is 0°C to 25°C; and / or The reaction temperature of the third reaction is 15°C-25°C; and / or The post-processing includes: Add ice to quench the reaction, precipitate to obtain a precipitate, let the layers stand, remove the water layer, wash the precipitate with water, evaporate the diluent, crush the precipitate in an alcohol solution or water, filter, wash with water, and dry to obtain the polyaryletherketone resin.

7. Use of the polyaryletherketone resin according to claim 1 or the polyaryletherketone resin obtained by the preparation method according to any one of claims 2 to 6 in preparing a polyaryletherketone resin-based composite material for fiber fabrics.

8. A polyaryletherketone resin-based prepreg for a fiber fabric, comprising: A fiber fabric and at least one polyaryletherketone resin selected from the polyaryletherketone resin of claim 1 or the polyaryletherketone resin prepared by the method of any one of claims 2 to 6; and The fiber fabric includes any one of carbon fiber, glass fiber, basalt fiber, boron nitride fiber, carbon nanotube fiber, graphene fiber or aramid fiber.

9. The polyaryletherketone resin-based prepreg of the fiber fabric according to claim 8, wherein the fiber fabric is in the shape of any one of plain fabric, twill fabric, satin fabric, three-dimensional woven fabric or unidirectional fiber.

10. A polyaryletherketone resin-based composite material for fiber fabrics, which is prepared by melting, hot pressing, cooling and solidifying the polyaryletherketone resin-based prepreg for fiber fabrics according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Method for preparing high molecular weight polyaryletherketone

    CN107987272A

  • Tert-butyl polyaryletherketone resin and preparation method thereof

    CN110437427A

  • Quaternary copolymerized polyaryletherketone as well as preparation method and application thereof

    CN112961340A